ANALISIS STRATEGI KEBERLANGSUNGAN BISNIS PT OFFBEATMUSIC INDONESIA - , Andhyka Andrian ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this research is to evaluate the business strategy and find the alternative product/service that still might be developed by PT. Offbeat Music Indonesia with the current condition of the music industry. The scope of this research is qualitative case study in PT. Offbeat Music Indonesia. The data used in this research is Primary and Secondary data. The Primary data is obtained by interviewing the resources, documentation, and observation. Primary data is also obtained from the music industry journal which published by the magazine expert and website. In this research, the researcher did two types of analysis, External analysis which will describe the competitiveness of Indonesia music industry and Internal analysis which linked by the analysis resources and the companyâs ability of using resources-based view analytical tool. The analysis externalâs tools used are five competitive forces, driving forces analysis, key success factor analysis, and PEST (Politic, Economy, Social, and Technology) analysis. The summary of this research shows that the business strategy used by PT. Offbeat Music Indonesia is focused with the off-air show, not in the physical album selling like the major label does. with experience and competency from PT. Offbeat Music Indonesia has a chance to broaden their business by doing the backward dan forward integration.